Os processos de criação publicitária e a formação profissional na contemporaneidade - Iahn, Roberta Cesarino (2011)
This research focuses on advertising, emphasizing the issues of message creation in contemporary brands and the creative processes that stimulate the professional formation of advertisers in Brazil. This study analyzes the repertories used in the development of the creative process of advertising professionals and the interferences they receive, calling attention to contributions from the fields of communication, education and culture. Creativity, imagination and originality are integrating elements of artistic composition that are also found in advertising campaigns. Creation in advertising, however, seems to establish a different or less important value. Frequently, the commercial and functional purpose of the activity devalues the repertory, the technique and the very act of creating messages and images stemming from so many aesthetic and cultural sources and references. The creative process of the advertising professional became calcified into stereotypes standardized by the media, thus ignoring the processes and network connections implied in the formation of the creative repertory. The daily routine of advertising agencies does not privilege the creative process of the message, stimulating the repetition of old formulas. The link between the university and the labor market is fragile, favoring detachment and superficiality in the formation of the young professional. Our main goal is to investigate the creative process of the advertising professional, questioning the cultural and aesthetic repertories used in the elaboration of messages. Setting, characters, lights and colors, elements aimed at intensifying the receiver s reactions, are part of the analysis, as well as the medias acting as a vehicle to those messages. The fields of activity of publicity are also important elements of the research, in order to reveal how the profession, in all its formats, demands strategy and creativity to be constitutive of its own essence. This research opens with a bibliographical selection of theoretical and scientific data pertaining to the theme. The methodological principles of genetic criticism are considered fundamental to understanding creation as an act of communication, as we analyze the ways through which the advertising professional takes cultural and aesthetic elements from his context, making them his own. This project is conducted under the scope of the research line Processos de Criação (Creative Processes), and shall enlarge its theoretical framework so as to include other theoretical proposals such as Edgar Morin s studies on complexity, concentrating on the matters of informational networks and mediation